Effects of Ro 31-8220 on lipopolysaccharides-induced hepatotoxicity and release of tumor necrosis factor from rat Kupffer cells - Lin Wen; Zhang Jun-Ping; Hu Zhen-Lin; Feng Zeng-Hui; Qian Ding-Hua (Acta Pharmacologica Sinica, 2016)
AIM: To investigate protein kinase C (PKC) functions on lipopolysaccharide (LPS)-induced hepatotoxicity, a new potent PKC inhibitor Ro 31-8220 (Ro) was used to detect its effect on LPS-induced hepatotoxicity in rat hepatocytes and tumor necrosis factor (TNF) release from rat Kupffer cells (KC). METHODS: Hepatocytes (containing KC) were incubated with LPS (10 mg.L-1) and Ro (0.1-10 mumol.L-1) for 24 h, alanine aminotransferase (AlaA) leakage in the culture as indication of hepatotoxicity. The TNF activity in the supernatant of rat KC culture with LPS in the presence of Ro (0.1-10 mumol.L-1) was monitored by the L929 target cell lytic assay. RESULTS: Ro (0.1-10 mumol.L-1) reduced AlaA leakage in the hepatocyte culture. Ro inhibited dose-dependently the LPS-induced TNF production from rat KC. CONCLUSION: PKC inhibitor Ro protects the hepatocytes from LPS-induced cytotoxicity and inhibits the LPS-induced TNF production from rat KC.